Curriculum Redesign to Increase Equity and Promote Active Citizenship in Science Education - Eleni A. Kyza; Yiannis Georgiou (Education Sciences)
Inequities are still present in the science classroom, often related to neglecting the needs of students from diverse backgrounds, insufficient attention to students’ interests, and unequal access to resources. This study examined the potential of a curriculum redesign strategy using the Socio-Scientific Inquiry-Based Inquiry Learning (SSIBL) pedagogical framework, for increasing students’ equitable participation in secondary school science classrooms, with a focus on girls’ equitable participation. Twelve chemistry education teachers and 294 students participated in this study. Using a mixed-methods experimental design with a pretest–posttest control group setup, students were assigned to the SSIBL group (n = 161) or to the Business-As-Usual (BAU) group (n = 133). Quantitative data from the classroom implementations of the redesigned SSIBL and BAU curricula and qualitative data from the teachers’ collaborative redesign meetings were collected and analyzed. The findings indicate that the curriculum redesign with an explicit equity-oriented focus was more effective than the BAU approach: the SSIBL curricula were more beneficial for girls, both in terms of scientific literacy and learning motivation. The findings of this study highlight the significance of the intentional design of learning environments to foster meaningful and equitable participation in students’ science learning as well as for teachers’ professional learning.